Monolith GaAsP/Si dual-junction solar cells grown by MBE. (December 2019) - Sobolev, M S; Ilkiv, I V; Lazarenko, A A; Mizerov, A M; Nikitina, E V; Pirogov, E V; Timoshnev, S N; Baranov, A I; Bouravleuv, A D
Abstract: The growth of monolith GaAsP/Si dual-junction solar cells on Si substrates by molecular-beam epitaxy is demonstrated. The technological method for the formation of a highly doped tunnel p + /n + junction was developed. An obvious increase in the value of the open-circuit voltage indicating the contribution of the top-junction in the total open-circuit voltage monolithic dual-junction solar cells was found.